Model Model UTAUT2 dalam Evaluasi Faktor-Faktor yang Mempengaruhi Niat Pembelian pada Konten Affiliate TikTok Shop - Devita Fahliza Ulfa; Arista Pratama; Siti Mukaromah (LKP Unity Academy, 2025)
The growth of TikTok Shop’s affiliate program provides opportunities for affiliates to earn commissions from uploaded content. However, the low purchase conversion rate indicates challenges in shaping BI. This study aims to analyze the factors influencing purchase intention in TikTok Shop affiliate content by adapting a modified UTAUT2 model. This research employed a quantitative approach through a survey of 410 respondents selected using purposive sampling, with the criteria of active TikTok users who had interacted with TikTok Shop affiliate content. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among variables in the research model. The results show that only PV has a significant effect on BI. Although EE and HT significantly affect HM, they do not directly influence BI. In addition, HM, TR, FC, and PE do not show a significant effect on BI. This study contributes by extending the application of the UTAUT2 model to the social commerce context, particularly TikTok Shop affiliate content, and emphasizes the importance of enhancing PV as the main factor in encouraging BI.